Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2021.744865
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Childhood Health Experience and Depression Among Older People: Evidence From China

Abstract: The assessment of childhood health experience helps to identify the risk of depression among older people. Poor childhood experience is generally associated with depression in adulthood. However, whether such association can be extended to older people’ life remains unclear. The history of parental mental health was obtained from 2014 CHARLS Wave 3 (Life History Survey) data while other data from 2011 CHARLS Wave 1 baseline data. The study involves 4,306 respondents. The depression was assessed by the Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This study found that poor childhood health conditions were risk factors for the emergence of depression in late life. Results from an observational study on childhood health and depression in older life by Min Yao and colleagues revealed clearly that poor childhood health conditions increase the odds of being depressed (17). Additionally, the results of this study strengthen the life course theory that early childhood adverse experiences have a signi cant impact on depression in late life (18,19,20).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This study found that poor childhood health conditions were risk factors for the emergence of depression in late life. Results from an observational study on childhood health and depression in older life by Min Yao and colleagues revealed clearly that poor childhood health conditions increase the odds of being depressed (17). Additionally, the results of this study strengthen the life course theory that early childhood adverse experiences have a signi cant impact on depression in late life (18,19,20).…”
Section: Discussionsupporting
confidence: 70%
“…Childhood health experience is considered as a risk factor for depression (17,18,19). Existing literature has highlighted that early detection of depression is inextricable from childhood experiences (20) because depression is jointly caused by biological, psychological, and social factors (21).…”
mentioning
confidence: 99%
“…Therefore, experiences in childhood might also have long-term in uences on health status in old age, both directly and indirectly. And it has been partially proved among empirical studies on cognition, depression and diseases in later life (Kendig et al 2017;Yao 2021;Zhang & Lu 2021;Zhang & Zhang 2022).…”
Section: Introductionmentioning
confidence: 97%
“…This study found that poor childhood health conditions were risk factors for the emergence of depression in late life. Results from an observational study on childhood health and depression in older life by Min Yao and colleagues revealed clearly that poor childhood health conditions increase the odds of being depressed [ 17 ]. Additionally, the results of this study strengthen the life course theory that early childhood adverse experiences have a significant impact on depression in late life [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood health experience is considered as a risk factor for depression [ 17 – 19 ]. Existing literature has highlighted that early detection of depression is inextricable from childhood experiences [ 20 ] because depression is jointly caused by biological, psychological, and social factors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%